Comparative study of modified Stoppa approach and ilioinguinal approach for pelviacetabular fractures - Abdul Aziz, Ansari Muqtadeer; Sonkawade, Venktesh D.; Santpure, Shivkumar (International Journal of Research in Orthopaedics, 2020)
Background: The present study was done to study advantages and disadvantages of modified Stoppa approach (MSA) and ilioinguinal approach (IIA) for surgery of pelviacetabular fractures involving anterior column, anterior wall, quadrilateral plate with protrusion and complex fractures, pelvic ring fractures with pubic diastasis or sacroiliac joint disruptions which needs to be stabilized anteriorly. Methods: Study was conducted in Department of Orthopaedics, Government Medical College and Hospital, Aurangabad on patients with pelviacetabular fractures during June 2018 to March 2020. In our study of 25 patients, they were divided into group A containing 13 patients operated using MSA and group B containing 12 patients operated using IIA. Follow up period was 12-18 months (mean=15) and 12-16 months (mean=14) for group A and B, respectively. Patients assessed using modified Merle d’Aubigné score and Matta’s score. Results: Mean modified Merle d’Aubigné score was 16 and 14 for group A and B, respectively (p value=0.89). Mean blood loss and operative time were less in MSA. Superficial infection was found in one patient each of group A and B whereas one patient developed deep infection in group B. One patient each of both group had hip pain suggestive of early arthrosis. In group B, two patients developed meralgia paresthetica. One patient developed external iliac artery thrombosis and inguinal hernia in group B. one patient from group A developed incisional hernia. Conclusions: MSA was better and simpler than IIA with due adequate training and practice to achieve direct access for pelviacetabular fracture reduction and also it requires less operative time, less blood loss and better postoperative outcome.